(3JWhjQ caGAI eLGdS GdEOGQI aj GdYGde GdYQHj (B( (3GdSge GdTGQO (B) /s - (3GdNWjH, eMeO eMj GdOjfs ((3YeGf(B: s (3GQ GdjGRhQj GdYdejI ddfTQ h GdJhRjY(B, s, 2008)
(3jVe gPG GdcJGH aj WjGJg eGjdj (B: (3HYO GdJbOje jYQV GdaUd GdChd GdJhLjg hJQc GdGOGQI ddeOQGA Ke aUd JYjjf CYVGA eLGdS GdGOGQI heYGjjQ Jbjjege hJbjje COGA GdeLdS hCYVGFg , Ke aUd GdhbJ de jaJ ddJYde CeG GdHGH GdKGfj aMed JHhjH GdJTcjd GdeKGdj deLdS GdEOGQI , GdYQa GdYGdej aj JTcjd eLGdS GdOGQI GdaUd GdKGfj CgejI CYVGA GdeSJbdjf ZjQ GdJfajPjjf , eGgh GdJTcjd GdeKGdj deLdS GdEOGQI hHhH GdHGH GdKGdK HhGLHGJ hGdJRGeGJ eLdS GdGOGQI QSe SjGSI GdTQcI hJMOjO GdQSGdI hGdQDjG HYjOI GdeOi hGdbje hVY GSJQGJLjI GdTQcI , GdGTQGa Ydi GdGOGQI GdJfajPjI , GdaUd GdQGHY JMed GdeSDhdjI JLGg GdeSGgejf hCUMGH GdeUdMIs
(3HjHdjhZQGajG U(B.167 (3GdedGMb U(B. 161s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQI GdYGeIs; (3GdEOGQI(B--(3JWhjQs; (3GdCbdjGJs; (3GdbjGOI GdEOGQjIs